New rhetorics for contemporary legal discourse - Condello, Angela, 1984- (Edinburgh University Press, 2020)
Are the general and the particular separated in legal rhetorics? What is the function of singular events, facts, names in legal argumentation and what is their relationship to legal normativity? This collection of 11 essays takes a diachronic approach to address these questions from the perspective of contemporary legal discourse.